Characteristics of electric performance and key factors of a hybrid piezo/triboelectric generator for wave energy harvesting. (March 2022) - Wardhana, Ede Mehta; Mutsuda, Hidemi; Tanaka, Yoshikazu; Nakashima, Takuji; Kanehira, Taiga; Maeda, Shuhei; Yamauchi, Masaaki
Abstract: Since the ocean energy field has a wide variety range of frequencies and amplitude, applying energy harvesters such as a piezoelectric generator (PEG) with a triboelectric generator (TEG) has been required for maximum result. Generally, energy harvesters can perform well due to the feature mechanism generation and the surface modification. However, few studies explain the relationship between characteristics of power generation with the device's key factors. This study proposed/developed a TEG into a multi-layered model, combined it with a PEG to form a PEG-TEG hybrid harvester, and demonstrated the improvement of the output voltage by modifying the key factors (i.e., acceleration amplitude, vibration amplitude, initial distance). We found that our hybrid harvester with the multi-layered TEG can improve the electrical energy output in linear terms under a comparatively small device. Furthermore, the key factors have much influence to generate electrical energy instead of compression force, suggesting that a small force is enough to produce a good result. Our result also showed that this linear improvement is possible due to the increase of vibration amplitude, indicating that amplitude adjustment is important, but it is not directly related to a good electrical performance for initial distance. Finally, the complementary relationship between devices was investigated, and it shows good compatibility. The study could be an essential finding and understanding for PEG-TEG hybrid energy harvesters to produce more efficient and sustainable harvesters in the ocean energy utilization.